Charcoal rot severity and yield components of common bean cultivars inoculated with Macrophomina phaseolina - Zanella,Eduardo José (2020)
ABSTRACT Macrophomina phaseolina is a soilborne pathogen with a wide range of hosts and its control through agricultural practices is difficult. The aim of this study was to quantify the severity of root rot (SRR) caused by M. phaseolina in common bean cultivars and its impact on yield components. The experiments were carried out under greenhouse conditions with the common bean cultivars ‘ANFC-9 Agro Norte’, ‘BRS Esteio’, ‘BRS Estilo’, ‘BRS Pérola’, ‘FTS Soberano’, ‘IPR Campos Gerais’, ‘IPR Tangará’, ‘IPR Tuiuiú’, ‘IPR Uirapurú’ and ‘TAA Dama’. Three isolates of M. phaseolina obtained from infected plants of common bean, soybeans and maize were inoculated in the common bean cultivars. In the phenological stage R9 of grain harvest maturity, the SRR and the yield components of root dry mass (RDM), number of pods per plant (NPP), number of grains per plant (NGP) and grain mass per plant (GMP) were assessed. All common bean cultivars were susceptible to M. phaseolina, showing a reduction in NPP, NGP and GMP. SPR was greater than 75%, regardless of the origin of isolates. Considering the average of cultivars, there was a significant decrease of 54.3% in RDM, compared to control treatments. The cultivars ‘IPR Tangará’, ‘ANFC-9 Agro Norte’, ‘BRS Esteio’, ‘BRS Pérola’ and ‘FTS Soberano’ had a decrease in at least one yield component, while a reduction occurred in all components for cultivar ‘IPR Tangará’. There was an average decrease in NPP, NGP and GMP of 7.9%, 7.6% and 7.2%; 13.4%, 12.8% and 6.7%; and 14.2%, 12.9% and 10.1%, considering the isolates obtained from beans, soybeans and maize, respectively.